2018
DOI: 10.1016/j.jsams.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Post marathon cardiac troponin T is associated with relative exercise intensity

Abstract: CTnT increases above reference limits during a marathon. Magnitude of cTnT rise is related to exercise intensity relative to ventilatory threshold and V˙Omax, but not individuals' absolute cardiopulmonary fitness, training state or running history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 28 publications
3
52
0
5
Order By: Relevance
“…The results concerning skeletal muscle damage, temporary decline of kidney function and inflammation markers after the Kalmar Ironman 2016 are in line with previous research in athletes engaging in either triathlon12 13 or other types of endurance sports such as marathon11 19 or ultradistance running 20. Given the amount of exercise, the results are neither surprising nor do they lead to any debate about long-term consequences.…”
Section: Discussionsupporting
confidence: 85%
“…The results concerning skeletal muscle damage, temporary decline of kidney function and inflammation markers after the Kalmar Ironman 2016 are in line with previous research in athletes engaging in either triathlon12 13 or other types of endurance sports such as marathon11 19 or ultradistance running 20. Given the amount of exercise, the results are neither surprising nor do they lead to any debate about long-term consequences.…”
Section: Discussionsupporting
confidence: 85%
“…Our findings for the effect of intensity of intermittent exercise are consistent with other studies, reviewed in the Introduction, showing greater elevation of cardiac biomarkers with higher intensity exercise. In particular, it obtained pronounced high-sensitivity cardiac troponin-T elevation after intermittent exercise with average heart rate of 160 min −1 , which was similar to the mean heart rate of our runners (Richardson et al, 2018). Stewart et al (2016) suggested that a heart rate of 145 min −1 was a threshold for the elevation of cardiac troponin.…”
Section: Discussionsupporting
confidence: 83%
“…A transient increase in myocardial membrane permeability appears to be responsible, but the mechanism is still under debate (Nie et al, 2010(Nie et al, , 2016Li et al, 2016b). Eijsvogels et al (2016) concluded that exercise intensity was the strongest single predictor of exerciseinduced cardiac troponin elevation, and Richardson et al (2018) found that cardiac troponin was associated with both mean and peak heart rate during exercise. Gresslien and Agewall (2016) hypothesized that there might be a threshold exercise intensity where cardiac troponin release became more marked.…”
Section: Introductionmentioning
confidence: 99%
“…Exhaustive exercise could cause myocardial cell edema and increased membrane permeability, and the rupture of myocardial fibers caused the release of cTn-I in cardiomyocyte to peripheral blood [21]. e acute overload exercise increased the level of cardiac calcium protein in the peripheral blood, and the increase of the serum myocardial injury marker enzyme was related to exercise intensity [22]. After EP, the content of myocardial enzyme in serum of exhausted rats decreased, which indicated that EP had the ability to resist the myocardial injury.…”
Section: Discussionmentioning
confidence: 99%